FINANCIAMENTO PÚBLICO E EXPANSÃO DA EDUCAÇÃO SUPERIOR FEDERAL NO BRASIL: O REUNI E AS PERSPECTIVAS PARA O REUNI 2 - Danilo de Melo Costa (Universidade Federal de Santa Catarina, 2013)
The Brazilian higher education is facing a major transformation that occurs through its restructuring and expansion. This paper presents and analyzes the actions of financing of the expansion of federal higher education in Brazil, which is based on two aspects: the creation of new universities and restructuring and expansion of existing universities. For this purpose, we chose as part of universities created after the year 2002 the University of Southern Frontier (UFFS), and as part of university restructured the Federal University of Santa Catarina (UFSC). So, we identified the perceptions of university leaders and understand the perspectives for financing and expansion of higher education in Brazil along with the public managers of the MEC. The research is exploratory-type with data processing predominantly qualitative. The results show that universities are receiving federal resources from the public financing and in the respective universities studied, this phenomenon was confirmed. All managers of both universities have recognized the importance and magnitude of such investments but believe that the continuity of the program, the Reuni 2, will be the differential to contribute to the development not only of the universities as the whole country.